Implementation of evidence-based, non-pharmacological interventions addressing behavior and psychological symptoms of dementia: a systematic review focused on implementation strategies. (16th September 2021) - Bennett, Sally; Laver, Kate; MacAndrew, Margaret; Beattie, Elizabeth; Clemson, Lindy; Runge, Catherine; Richardson, Laura
ABSTRACT: Objective: This study aimed to identify the nature and effects of implementation strategies to increase the use of evidence-based, non-pharmacological interventions designed to reduce the frequency and/or severity of behavioral and psychological symptoms associated with dementia, for people living in the community. Design: This was a systematic review of implementation studies. We searched six databases (in January 2019) and hand-searched reference lists of reports. Studies were included if they used quantitative methods evaluating the use of implementation strategies to increase the use of non-pharmacological interventions. These interventions had to have been tested in a randomized controlled trial (RCT) and found to reduce behavioral and psychological symptoms of dementia, for those living in the community. Studies needed to report the effect of the implementation on clinical practice, for example, a change in practice or the adoption of the intervention in community settings. Results: Twelve studies were included: 11 one-group pre-post design studies and 1 cluster RCT. All studies reported practice change – the majority implementing a new intervention, with six different types of interventions implemented. All studies reported including using partnerships, new funding, educational strategies, and ongoing support and consultation. Seven implementation studies reported positive outcomes for clients on some aspect of behavior or depression for the person with dementia. Conclusions: Implementation studies using multiple implementation strategies to increase the use of non-pharmacological interventions have demonstrated improvements in behavioral and psychological symptoms common in people with dementia, when provided by clinicians as part of their everyday work routines.